Feasibility of Rehet Iced Tea Shop in North Cikarang: Opportunities and Strategic Challenges - Putriani, Lira; Andini, Nadya Shafa; Padilah, Aditia Tri; Maulana, Fiqri; Setiawan, Aris; Mozart, Mohammad (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the opportunities and challenges of the Rehet Ice Tea Shop business feasibility in North Cikarang. Using a qualitative approach, data were collected through interviews, observations, documentation, and literature studies. The analysis results indicate that Rehet Ice Tea Shop has significant marketing opportunities, including a broad market segment, competitive prices, a strategic location, and the use of social media as a promotional tool. However, significant challenges arise from intense competition with similar businesses. This shop is required to continue to innovate in products and services to maintain competitiveness in the market. Revenue data for the past six months indicates sales fluctuations influenced by external factors such as national day celebrations. The conclusion of this study confirms that effective marketing strategies and product innovation are key to the sustainability of Rehet Ice Tea Shop's business in facing competition in the modern beverage MSME sector.